Árvore araputanga - Santos, Silvana Ramos dos; Silva, Ana Carla Ferreira da; Bento, Miriam Furtado; Schiavinato, Ricardo Leandro; Lima, Eliene Xavier de; Oliveira, Maria Auxiliadora de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf